(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this current investigation, we apply Horadam polynomial to establish sharp upper bound for the second and third coefficient of functions from new subclass of sakaguchi type bi-univalent functions defined in the open unit disk . Also, we discuss Fekete-Szego inequality for functions belongs to this subclass.